Development of Leishmania mexicana in Lutzomyia longipalpis in the absence of sugar feeding - Costa, Samara G. da (2019)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica e Fisiologia de Insetos. Rio de Janeiro, RJ, Brasil.